Cortical Morphometry and Its Relationship with Cognitive Functions in Children after non-CNS Cancer. (19th May 2021) - Spitzhüttl, Janine S.; Kronbichler, Martin; Kronbichler, Lisa; Benzing, Valentin; Siegwart, Valerie; Schmidt, Mirko; Pastore-Wapp, Manuela; Kiefer, Claus; Slavova, Nedelina; Grotzer, Michael; Steinlin, Maja; Roebers, Claudia M.; et al.
ABSTRACT: Background : Childhood cancer survivors (Ccs) are at risk for cognitive late-effects, which might result from cortical alterations, even if cancer does not affect the brain. The study aimed to examine gray and white matter volume and its relationship to cognition. Methods : Forty-three Ccs of non-central nervous system cancers and 43 healthy controls, aged 7–16 years, were examined. Cognitive functions and fine motor coordination were assessed and T1-weighted images were collected for voxel-based morphometry. Results : Executive functions ( p = .024, d = .31) were poorer in Ccs than controls, however still within the normal range. The volume of the amygdala ( p = .011, ŋ 2 = .117) and the striatum ( p = .03, ŋ 2 = .102) was reduced in Ccs. No significant structure–function correlations were found, neither in patients nor controls. Conclusion : Non-CNS childhood cancer and its treatment impacts on brain structures relevant to emotion processing.